Analysis and Modeling of Direct Ammonia Fuel Cells for Solar and Wind Power Leveling in Smart Grid Applications - Miswar A. Syed; Osamah Siddiqui; Mehrdad Kazerani; Muhammad Khalid (IEEE Access)
Integration of wind and solar energy sources in power systems causes frequency and voltage-related power quality issues, especially at high penetration levels. Battery energy storage systems help reduce fluctuations by absorbing excess power and delivering power deficits. However, batteries suffer from capacity fading and degradation due to frequent cycling. Storing energy in the form of a chemical fuel helps in overcoming these drawbacks. Since ammonia fuel cells address issues associated with hydrogen fuel cells, such as high flammability, poor volumetric density, and high storage costs, in this study the application of ammonia fuel cells for solar and wind power leveling is investigated. Excess wind/solar power is used in an electrochemical ammonia synthesizer (EAS) to produce ammonia, and a direct ammonia fuel cell (DAFC) converts the ammonia to electric power and supplies the power deficit. Smoothing filter concepts, such as moving average, moving median, Savitzky-Golay, moving regression (MR), and Gaussian filters, are employed to assess EAS and DAFC capacity requirements. Simulation results show that MR filter’s overall performance is superior to those of other smoothing filter approaches, resulting in reduced required capacities for ammonia production and fuel cell output, lowering system costs. The developed energy storage system is an effective compensation method for solar and wind power fluctuations.